Biochemical indices of calcium homeostasis as a biomarker of mixed toxic occupational exposure. - Adunmo, G.O.*, Anetor, J.I., Adesokan, A.A. , , Adunmo E.O. (Sokoto Journal of Medical Laboratory Science)
Exposure to a single chemical and associated disorder in occupational environment has received a tremendous attention but unlike laboratory animals, people hardly get exposed to a single chemical agent and thus the need to examine possible alteration in biochemicals parameters in the subjects exposed to mixed chemicals. Alteration in calcium homeostasis has been associated with cell transformation in the process of carcinogenesis. The aim of this study was to explore the effect of occupational chemical exposure on calcium homeostasis. Sixty-six (66) exposed subjects (aged 21- 70) were selected. They comprised mechanics (41), panel beaters (12), welders (7) and painters (6) within Ibadan metropolis working together within the same environment. The mean duration of occupational exposures was 14.85+ 8.85 years. Twenty-five males, apparently healthy non-exposed individuals, were observed as controls. Biochemical indicators of calcium homeostasis were evaluated in all subjects. Total Calcium, albumin, total protein and uric acid were determined spectrophotometrically, while ionized calcium and globulin were calculated. Ionized calcium level was significantly decreased (p< 0.05) in the exposed group compared with the controls. Total calcium though reduced in the exposed group compared with controls was not significantly altered (p>0.05). Inorganic phosphate, like ionized calcium was significantly decreased in the exposed groups compared with the controls (p<0.05). Alkaline phosphate and globulin were significantly raised (p<0.05) in the exposed group . Uric acid was not significantly altered (p>0.05).The results supports alteration in calcium homeostasis in the exposed group and might be associated with cell transformation and the risk of carcinogenic process.